Digital image forgery detection - Tay, Qinyuan. (2011)
Digital image forgery has become a widespread phenomenon in today’s society. Digital images are easy to manipulate and edit due to availability of powerful image processing and editing software. It is possible to add or remove important features from an image without leaving any obvious traces of tampering. As digital cameras and video cameras replace their analog counterparts, there is a pressing need for authenticating digital images, validating their content and detection of forgeries.